Shikonin contributes to intestinal epithelial cell differentiation through PKM2/NRF2-mediated Polyol pathway - Ling Huang; Xiufu Tang; FangYing Yang; Wenxu Pan; Xinhua Liang; Zhaohui Xu; Meiwan Cao; Junhong Zhao; Huan Chen; Jing Huang; Jiayu Chen; Lanlan Geng; et al. (Elsevier, 2021)
Background: Alteration of polyol pathway is a critical event in serials of disease, including inflammatory bowel disease (IBD). Shikonin, an inhibitor of PKM2, has been reported to exert a wide range of biological and pharmacological properties. However, the function of shikonin-mediated polyol pathway in IBD remained to be addressed. Methods: We conducted WB and qPCR to analyze the effect of shikonin on intestinal epithelial cell differentiation. IF, IP, luciferase assay and ChIP were employed to demonstrate the mechanism that shikonin regulated cell differentiation through polyol pathway. Elisa was used to measure the serum sorbitol in subjects enrolled in this study, and the clinical sample was collected to detect PKM2, AR and NRF2 expression. Results: Herein, we showed that shikonin treatment in HT-29 and CaCO2 cells not only contributed to CDX2 and its targets expression, including MUC2 and villin, leading to cell differentiation, but also induced NRF2-mediated AKR1B1 and AKR1B10 expression, resulting in increasing AR activity. A synergistic effect on CDX2-mediated cell differentiation was observed in CaCO2 cells in response to cotreatment with shikonin and AR agonist bortezomib for 24 hours, while aldose reductase inhibitor fidarestat treatment in CaCO2 cells reversed the enhanced CDX2 expression caused by shikonin. Mechanistically, PKM2 interacted with NRF2, and this interaction was enhanced in response to shikonin stimulation, resulting in NRF2 phosphorylation and nuclear translocation, which further increased AKR1B1 and AKR1B10 transactivation. Moreover, both AKR1B1 and AKR1B10 expression were decreased, while PKM2 was increased in intestinal epithelial cells labeled with E-cadherin in patients with IBD, and a negative clinical relationship was observed between PKM2 and AKR1B1/AKR1B10, respectively. What's more, the serum sorbitol level was decreased in patients with IBD. Conclusion: These results suggested that shikonin could promote intestinal cell differentiation through NRF2-mediated polyol pathway, implying that shikonin may be a promising therapeutic drug for the treatment of IBD.